To Share or Not to Share: Does Local Participation Matter for Spillovers from Foreign Direct Investment? - Smarzynska Javorcik, Beata; Spatareanu, Mariana (2012)
This study hypothesizes that the ownership structure in foreign investment projects affects the extent of vertical and horizontal spillovers from foreign direct investment (FDI) for two reasons. First, affiliates with joint domestic and foreign ownership may face lower costs of finding local suppliers of intermediates and thus may be more likely to engage in local sourcing than wholly owned foreign subsidiaries. This in turn may lead to higher productivity spillovers to local producers in the supplying sectors (vertical spillovers). Second, the fact that multinationals tend to transfer less sophisticated technologies to their partially owned affiliates than to wholly owned subsidiaries, combined with the better access to knowledge through the participation of the local shareholder in partially owned projects, may facilitate more knowledge absorption by local firms in the same sector (horizontal spillovers). The analysis based on a Romanian firm-level data set produces evidence consistent with these hypotheses. The results suggest that vertical spillovers are associated with projects with shared domestic and foreign ownership but not with fully owned foreign subsidiaries. They also indicate that the negative competition effect of FDI inflows is lower in the case of partially owned foreign investments as it is mitigated by larger knowledge dissipation within the sector.